Ramadan fasting and sports performance: A Malaysian perspective - Ooi, Cheong Hwa; Roy, Jolly; Mohd Ghazali, M. Z.; Loo, Lean Hiong; Ahmad Padzi, M. N.; Chai, Wen Jin; Md Razali, Mohd Rizal; Feizal, Victor; Aziz, Abdul Rashid; Singh, Rabindarjeet (National lnstitute of Education (Singapore), 2010)
The purpose of this study was to identify factors that would affect Muslim athletes in their training or competition during the Ramadan fast. This would lead to a better understanding of the changes in lifestyle, behavioural and training practices of Muslim athletes when they participate in Ramadan fasting and exercise at the same time. A total of 172 Malaysian Muslim national elite athletes participated in a questionnaire survey assessing personal perception on sport performance, sleep pattern, food and fluid intake during Ramadan fasting. The results showed that a quarter of these athletes perceived that there was an adverse effect from the Ramadan fast on their sport performance. A majority of them (58.1%) said that Ramadan fasting did not affect their sleep pattern but 52.3% of them did take an extra nap during the daytime. Most of the athletes (45.9%) ate the same amount of calories as they normally would however 86.0 % believed that they drank more fluids than usual. The changes in lifestyle during the Ramadan fast did not adversely affect the perceived sport performance in this cohort of Muslim elite athletes. However, there is an equivocal opinion on the impact of Ramadan fasting on the quality of training.